Snowboard landings from different heights: electroencephalography activity in motor preparation and lower limb electromyography changes - Ouyang, B.; Chen, J. (Perceptual and Motor Skills, 2023)
The neural strategies for movements of the lower extremities for landings from different landing heights in trained half-pipe snowboarders are not well known. We observed changes in brain activity as measured by electroencephalography (EEG) and lower limb muscle activity as measured by electromyography (EMG) in trained and untrained half-pipe snowboarders landing from different heights (30 and 60 cm). There were 12 trained male half-pipe snowboarders (HS) and 12 untrained participants (UP). We recorded EEG signals during motor preparation prior to dropping and EMG signals from right lateral rectus femoris (RF), tibialis anterior (TA), and gastrocnemius lateralis (GL) muscles during landings. Generally, theta power in the frontal cortex significantly increased in the preparation period compared to the resting state, while the alpha 1 and alpha 2 power values in central and parietal cortical areas decreased as dropping heights increased. Additionally, the HS group displayed greater magnitudes of change in power values in three frequency bands compared to the UP group. The HS group (relative to UP group) also showed higher normalized EMG amplitudes for RF and GL during contact, especially at 60 cm. The HS group (relative to the UP group) presented lower antagonist EMG activity and a higher GL/TA ratio at the 60 cm dropping height. Long-term specialized training might lead to greater neural modulation of predictive sensorimotor control and specific neuromuscular activation patterns during landing.